An Overview of Reviews as a Trend Maker in the Field - L. K. Raitskaya; E. V. Tikhonova (Moscow Polytechnic University, 2020)
The authors consider the methodology basics of reviews as a prospective type of scholarly publications, their taxonomy and most popular review types (narrative reviews, bibliometric reviews, systematic reviews, reviews of reviews, scoping reviews, meta-analysis), as well as specific features of procedures and algorithms for conducting reviews. Top 100 of highly cited reviews on higher education from 2010 to 2019 published in high-ranking peer-reviewed journals and indexed in the international database Scopus is based on the traditional methodology that aims to sample the most essential and influential publications of the kind in a well-represented and unbiased way and to subject the sampled reviews to content, bibliometric, and linguistic analyses. based on the inclusion criteria, keywords and methods of objective selection and sampling of the publications to be reviewed and analyzed, the authors singled out the essential thematic clusters in Top-100 list (educational technologies, university, student, teaching, learning, assessment, etc.) and determined the key directions in the review field of study. Each cluster contains a brief description of the most important aspects and approaches to various topics related to higher education, an analysis of their novelty and existing gaps in the field. According to the rhetoric theory of scholarly text by John Swales named 'Moves and steps', the authors offer a uniform rhetoric schema of reviews, commenting on the text components and their contents. Such a schema may serve as a guideline for authors of reviews made up for international peer-reviewed journals. The most popular publications by citations and number of publications entail reviews devoted to the culture of higher education; educational technologies and peculiarities of their application in the new educational landscape; online education as a new dimension of education requiring a special ecosystem; academic ethics of university teachers; soft skills development necessary for successful professional development; academic and scientific libraries as new centers for scientific and academic communication.